Peer Guidance untuk Mereduksi Perilaku Bullying Pada Remaja Muhammadiyah - Amien Wahyudi; Agus Supriyanto; Hardi Prasetiawan (Universitas Muhammadiyah Pringsewu, 2018)
Bullying behavior because the victim experiences poverty or physical disability. The impact of bullying is self-esteem and affects maturity in students. School counselors have a role for skills, as well as collaborative efforts with the Peer Guidance approach. The method used in peer guidance training: (1) education, (2) training, (3) forum group discussion, and (4) brainstorming. Peer guidance to train actors to have empathy for the whole individual skills to listen, guide, reflection, conclude, confrontation, interpreating, and support. Peer guidance skills are used by students, offenders, or victims to prevent bullying.Keywords: berhaviour, bullying, peer guidance